TRANSLATION STRATEGIES IN ENGLISH-INDONESIA STORY ENTITLED THE IMPORTANCE OF FULFILLING PROMISES - Dian Wulandari (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This research is about translation strategies that are found in short story entitled The Importance of Fulfilling Promise. According to Chesterman (1997), there are three types of translation strategy, namely syntactic strategy, semantic strategy and pragmatic strategy. The problem of the research is what translation strategies that are used in English-Indonesia translation of short story entitled The Importance of Fulfilling Promises. The objective of the research is to find out what translation strategies that are used in English-Indonesia translation of short story entitled The Importance of Fulfilling Promises. The writer used descriptive qualitative method in analyzing the data. After the writer analyzed the data, the writer found 21 of translation strategy that the translator used in translating a short story entitled The Importance of Fulfilling Promise, namely 9 syntactic strategy (2 literal translation, 2 calque, 2 phrase structure change, 2 cohesion change, 1 sentence structure change), 4 semantic strategy (2 synonymy and 2 emphasis change), and 8 pragmatic strategy (6 explicitness change and 2 illocutionary). Therefore, the total of data that the writer found is 21 data translation strategy.